Cultural Adaptation of Business Expatriates in the Host Marketplace - Jun, Sunkyu; Gentry, James W.; Hyun, Yong J. (Journal of International Business Studies, 2001)
Satisfaction with the host culture has been found to influence the expatriate's commitment to the local operation and to the parent company. This paper investigates the role that the expatriate's consumer experiences play in the determination of his/her satisfaction with the new culture. Market alienation has a negative effect on satisfaction, but it is reduced by participation in the host marketplace. Further, cultural knowledge was not found to be directly related to satisfaction with the host culture, but rather was related indirectly through its association with participation in the host marketplace.